Hearing From Men Living With HIV: Experiences With HIV Testing, Treatment, and Viral Load Suppression in Four High-Prevalence Countries in Sub-Saharan Africa - Wiginton, John Mark; Mathur, Sanyukta; Gottert, Ann; Pilgrim, Nanlesta; Pulerwitz, Julie (Frontiers in Public Health, 2022)
Engaging men in HIV services remains a challenge across sub-Saharan Africa. There is a critical need to better understand facilitators of men’s successful engagement with HIV services and assess if there are similarities across contexts. We conducted in-depth interviews and focus group discussions with 92 men living with HIV (MLHIV) across Malawi, Uganda, South Africa, and Eswatini, most of whom had been diagnosed with HIV within the last five years. We coded interviews for themes using a constant-comparative approach. We contextualized our findings within a socioecological framework. HIV testing was primarily motivated by illness (individual level), though illness was sometimes accompanied by prompting and support from healthcare providers and/or intimate partners. Once diagnosed, nearly all participants reported immediate linkage to care, initiation of antiretroviral therapy (ART), and subsequent ART adherence. ART initiation and adherence were facilitated by men’s sense of agency and ownership over their health (individual level), social support from intimate partners, friends, and family (interpersonal/network level), supportive-directive counseling from healthcare providers (institutional/health systems level), and male-friendly services, i.e. rapid, respectful, private (institutional/health systems level). Health literacy regarding viral suppression (individual level), strengthened by patient-provider communication (institutional/health systems level), was highest in Uganda, where most men could discuss viral load testing experiences, report their viral load status (most reported suppressed), and demonstrate an understanding of treatment as prevention. Elsewhere, few participants understood what viral load suppression was and even fewer knew their viral load status. Our findings reveal socioecological-level facilitators of men’s progress across the HIV-care continuum. Programs may want to leverage facilitators of ART initiation and adherence that span socioecological levels – e.g., healthcare ownership and agency, social support, supportive-directive counseling – and apply them to each end of the continuum to encourage early HIV testing/diagnosis and improve health literacy to help men understand and achieve viral load suppression.